Implementation of the Jigsaw Type Cooperative Learning Model on Improving Achievement and Learning Motivation of Muhammadiyah in Mu'allimin Madrasah Muhammadiyah Yogyakarta - Fanani, Istiqlal Yul; Prakoso, Riyan Dwi Yulian; Bissessar, Charmaine; Gligorovic, Milica (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This research aims to determine the enhancement of students ' achievement and motivation after action, to know the difference in achievement and motivation to learn in the subjects of the youth through cooperative learning model of the jigsaw type, describing the constraints of teachers in using the type of cooperative learning model in Class 3 A Madrasah mu'allimin Muhammadiyah Yogyakarta. This research is a collaborative class of action research. The subject of the study was a Grade 3 student of A Madrasah Tsanawiyah mu'allimin Muhammadiyah Yogyakarta 2021/2022 as many as 31 students. This research is focused on the achievement and motivation to learn the Kemuhammadiyahan after implementing a model of type cooperative learning. Data collection techniques using observation, documentation, and tests. The data analysis techniques on this study used quantitative and qualitative descriptive. Based on the results of the study of achievement and motivation to learn students of Grade 3 A Madrasah Tsanawiyah mu'allimin Muhammadiyah Yogyakarta in the learning of the youth from before the action, cycle I and cycle II through the implementation of the learning model The jigsaw type cooperative experienced a very significant improvement.